Exposure assessment and risk characterization of aflatoxin M1 through consumption of market milk and milk products in Ludhiana, Punjab. (August 2021) - Kaur, Simranjot; Bedi, Jasbir Singh; Dhaka, Pankaj; Vijay, Deepthi; Aulakh, Rabinder Singh
Abstract: The present study was conducted with the objectives to evaluate the prevalence of AFM1 in market milk and milk products from Ludhiana district of Punjab. A total of 408 samples comprising of milk (n = 109), butter (n = 97), cheese (n = 99) and curd (n = 103) were collected from seven tehsils of Ludhiana. The samples were tested for the estimation of aflatoxin M1 (AFM1) using ELISA technique; of which, 10% of the positive samples were confirmed by high performance liquid chromatography (HPLC). Further, the estimation of exposure and risk characterization of the consumer population of Ludhiana district to AFM1 from milk and milk products was done using deterministic and probabilistic methods. Overall, the mean levels (ppb) of AFM1 in milk, butter, cheese and curd were 0.314 ± 0.35, 0.100 ± 0.15, 0.321 ± 0.41 and 0.162 ± 0.22, respectively. The estimated daily intake (EDI: ng/kg body weight/day) of AFM1 among the consumers due to consumption of milk, butter, cheese and curd was 2.303, 0.020, 0.068 and 0.3287, respectively. Among the different income groups of consumers, the quantities of AFM1 consumed per day through milk and milk products were significantly higher in 'high income group'. The risk of hepatocellular carcinoma (HCC) cases/year/10 5 individuals of different age groups showed that the value of HCC using deterministic approach was maximum (0.0106) in the age group '1–9 years' and least (0.0020) in age group '21–60 years'. The Hazard Index (HI) value was found high for milk (11.54) and curd (1.64) as compared to butter (0.10) and cheese (0.34). The health risk assessment indicated that consumers, especially children, in the study area are at comparatively higher health risk to AFM1 owing to their low body weight and higher milk intake. The present study revealed the urgent need to control the occurrence of aflatoxins in milk through continuous monitoring and regular inspection to reduce the exposure among the consumer population. Highlights: AFM1 presence was observed in market milk and milk products in Ludhiana, Punjab. Risk characterization indicates AFM1 in milk may pose health risk. The results warrants monitoring and control of aflatoxins in animal feed.